Relational Databases And Their Applications - Sobirjonov, Behzod Qahramonivich; Usipaliyeva, Madinaxon; Husanova, Shahloxon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article examines the fundamental principles of relational databases, their structure, and their practical application areas. It analyzes the advantages of the relational model, data integrity and security, as well as efficient information management through table relationships. The paper also highlights the role of relational database systems in modern information technologies, their usage fields, and real-world applications.